Uric acid and metabolic syndrome: Findings from national health and nutrition examination survey - Bowden, Rodney G.; Richardson, Kathleen A.; Richardson, Luke T. (Frontiers in Medicine, 2022)
Introduction Hyperuricemia commonly associated with Gout has been proposed as an independent risk factor for Metabolic Syndrome (MetS). Objective The purpose of the study was to determine if there is a relationship between hyperuricemia and MetS. Methods An analysis of cross-sectional data was conducted using the 2013–2018 National Health and Nutrition Examination Survey (NHANES) datasets. Sample weights were assigned by NHANES researchers to each participant allowing researchers to generalize results to all non-institutionalized United States (US) civilians. The analysis included 6,432 individuals, which were representative of 94,729,059 US citizens. Results Pearson’s correlations, chi-square tests, and logistic regression equations were calculated to determine the association between hyperuricemia and MetS. In an unadjusted regression analysis, individuals with hyperuricemia (above 7.0 mg/dL in males and 6.0 mg/dL in females) were 3.19 times more likely to have MetS compared to those with normal uric acid (UA) levels. When controlling for various confounding variables those with hyperuricemia were 1.89 and 1.34 times more likely to have MetS than those with normal UA levels in two additional logistic regression models. Conclusion In this large cross-sectional study, hyperuricemia was found to be associated with MetS. Additional analyses that controlled for various risk factors previously identified as predictive of MetS still demonstrated hyperuricemia independently associated with MetS. The results of this study suggest a need to understand the metabolic pathways of UA more clearly to further explain the contribution to MetS. Additional research should include prospective clinical trials assessing the effects of UA and the control of UA on MetS and concomitant medical outcomes.